Endothelin1 Levels in Pregnant Women with Severe Preeclampsia and Normal Pregnant Women - Wijaya, Yosiana; Wantania, John JE; Laihad, Bismarck J (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To determine the ratio of serum endothelin-1 levels between severe preeclampsia and normotensive pregnancy. Methods: Observational analytic study using cross-sectional. Sixteen woman with normal pregnancy and sixteen others with severe preeclampsia who met the inclusion and exclusion criteria, were tested for ET-1. The serum was analyzed at Prodia Laboratory, Manado. The ET-1 level was examined using ELISA (R&D Systems, Inc., Minneapolis, MN 55413, USA). The data obtained was analyzed using SPSS software version 20.0.and discussions were held using the existing literature theory. Results: The mean and median levels of endothelin-1 plasma in patients with severe preeclampsia is 2:46 ± 1:44 pg/ml, 1:09 ±  0:26 pg/ml, whereas in normotensive pregnancy is 1:03 ±  0:26 pg/ml, 1.95 ± 1:44 pg/ml with p < 0:05 (0000). Conclusion: There was a significant difference between endothelin- 1 level in severe preeclampsia and normotensive pregnancies. [Indones J Obstet Gynecol 2017; 5-2: 77-82] Keywords: endothelin-1, normotensive, preeclampsia